Three planets around HD 27894: a close-in pair with a 2 : 1 period ratio and an eccentric Jovian planet at 5.4 AU - Trifonov, Trifon; Reffert, Sabine; Brems, Stefan S. (Astronomy letters, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics